Development of STAFA Interactive Learning Multimedia for Science Subjects in Grade X of Senior High School - Phito, Veldry; Zen, Zelhendri; Bentri, Alwen; Rahmi, Ulfia (LPPM Universitas Jambi, 2026)
Education is the main foundation for facing the flow of globalization and the development of the industrial revolution towards society 5.0. Therefore, the education system continues to transform and expand the use of digital technology. One way to do this is to present digital learning content through the development of interactive learning multimedia. The results of the study indicate that the science learning media used in high school classes remain one-way and teacher-centered. Therefore, the purpose of this study is to develop an interactive multimedia STAFA that is valid, practical, and effective in improving student learning outcomes. This study uses the Research and Development (R&D) method using the ADDIE model. The research subjects were class X E2 students at SMAN 1 Siberut Tengah. Research data was obtained from students, teachers, and a team of experts who were then tested for validity, practicality, and effectiveness. The results of this study are interactive multimedia STAFA that are valid, practical, and efficient. Media experts gave an average product validity score of 97%, material experts 89%, and language experts 99%. All experts gave scores in the very valid category. The results for teacher responses were 95% and for students, 90%, in the very practical category. The effectiveness of media on learning outcomes shows an N-Gain score of 0.60, indicating a moderate and effective effect on the learning process.